Inheritance law: a comparative study in the framework of private international law - Oyunaa, Tserendagva (Journal of the Belarusian State University. Law, 2025)
The article examines the legal basis of Roman inheritance law and the inheritance law of the Mongol Empire, Qing dynasty, Mongolian People’s Republic and the inheritance law in the legislation of Mongolia during the transition to the market economy.
Keywords: Roman private law; inheritance law of Mongolia; inheritance by law; will; heir; international private law